PENGARUH CITRA MEREK DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PT. SERASI AUTO RAYA JAKARTA - Meilly Yanni Yanwar; Tatag Herbayu (Jurnal Manajemen Bisnis Krisnadwipayana, 2021)
To determine the effect of brand image and service quality on customer satisfaction PT. Serasi Auto Raya (SERA) Jakarta. This research uses quantitative methods. The population of this research is the customers of PT. Serasi Auto Raya (SERA) Jakarta with a total sample of 80 respondents who were taken using a sampling technique using incidental sampling techniques, by filling out a questionnaire on google form. The analysis technique was carried out with simultaneous and partially linear regression. Based on the test results, it is found that brand image has a positive and significant effect on customer satisfaction. Then, service quality has a positive and significant effect on customer satisfaction. Furthermore, brand image and customer satisfaction simultaneously have a significant effect on customer satisfaction at PT. Serasi Auto Raya (SERA) Jakarta.